Self-efficacy, performance, training and well-being of industrial workers in Lagos, Nigeria (2013)
The main purpose of this study was to investigate whether Self- Efficacy (SE) has anything to do with industrial employees’ training, performance and well-being in Nigeria industrial settings. Self-Efficacy (belief about one’s ability to accomplish specific tasks) form a central role in the regulatory process through which an individual’s motivation and performance are governed. It also affects employees’ training and well-being. The descriptive survey research design of the ex-post facto type was adopted. The population for the study consisted of employees of SKG Lagos, Glaxo, Ikeja and Smithkline Beecham, Ogba. The simple random sampling technique was used to select 274 respondents for the study. Four research instruments structured on a modified four point rating format of Strongly Agree (SA)=4, Agree (A)=3, Disagree (D)=2. Strongly Disagree (SD) =1 were used and having reliability coefficient of: Self-Efficacy Scale (SES)=0.85; Training Acquisition Scale (TAS)=0.80; Work Performance Scale (WPS)=0.82 and Well-being Scale (WBS)=0.87. Data were analyzed with t-test statistic. The finding revealed that workers with high self-efficacy are higher performers of assigned duties than those with low self – efficacy, workers with high level of self-efficacy are more amenable to training than those with low level of self – efficacy and workers with high self-efficacy are better in their well-being than those with low self – efficacy. It was recommended that industrial social worker should work on the psychic of the workers so that their self-efficacy can be developed or strengthen positively with the intent of promoting higher performance, adaptability to training and fostering of employees well-being.